Comparative Analysis of Verbal and Non-Verbal Mental Activity Components Regarding the Young People with Different Intellectual Levels - Y. M. Revenko; V. A. Salnikov (Russian State Vocational Pedagogical University, 2015)
The paper maintains that for developing the educational pro- grams and technologies adequate to the different stages of students' growth and maturity, there is a need for exploring the natural determinants of intel- lectual development as well as the students' individual qualities affecting the cognition process. The authors investigate the differences of the intellect manifestations with the reference to the gender principle, and analyze the correlations be- tween verbal and non-verbal components in boys and girls' mental activity depending on their general intellect potential. The research, carried out in Si- berian State Automobile Road Academy and focused on the first year stu- dents, demonstrates the absence of gender differences in students' general in- tellect levels; though, there are some other conformities: the male students of different intellectual levels show the same correlation coefficient of verbal and non-verbal intellect while the female ones have the same correlation only at the high intellect level. In conclusion, the authors emphasize the need for the integral ap- proach to raising students' mental abilities considering the close interrelation between the verbal and non-verbal component development. The teaching materials should stimulate different mental qualities by differentiating the educational process to develop students' individual abilities.